The Appeal of Soka Gakkai in the United States: Emergent Transmodernism - Machachek, David W. (Research in the social scientific study of religion, 1999)
The Soka Gakkai is a Japanese Buddhist sect that has experienced remarkable success in the United States. Since the foundation of SGI-USA in 1960, it has transformed itself from a religion of immigrants to one composed primarily of non-Japanese converts. This paper presents a preliminary analysis of data from the 1997 SGI-USA membership survey. These data are consistent with the hypothesis that the appeal of Soka Gakkai to Americans may be found in the affinity between SGI philosophy and a "Transmodem" subculture emerging in advanced industrial society.